Real‐life effectiveness of omalizumab in severe allergic asthma above the recommended dosing range criteria. Issue 11 (22nd July 2016) - Hew, M.; Gillman, A.; Sutherland, M.; Wark, P.; Bowden, J.; Guo, M.; Reddel, H. K.; Jenkins, C.; Marks, G. B.; Thien, F.; Rimmer, J.; Katsoulotos, G. P.; et al.
Summary: Background: Omalizumab (Xolair) dosing in severe allergic asthma is based on serum IgE and bodyweight. In Australia, patients eligible for omalizumab but exceeding recommended ranges for IgE (30–1500 IU/mL) and bodyweight (30–150 kg) may still receive a ceiling dose of 750 mg/4 weeks. About 62% of patients receiving government‐subsidized omalizumab are enrolled in the Australian Xolair Registry (AXR). Objectives: To determine whether AXR participants above the recommended dosing ranges benefit from omalizumab and to compare their response to within‐range participants. Methods: Data were stratified according to dose range status (above‐range or within‐range). Further sub‐analyses were conducted according to the reason for being above the dosing range (IgE only vs. IgE and weight). Results: Data for 179 participants were analysed. About 55 (31%) were above recommended dosing criteria; other characteristics were similar to within‐range participants. Above‐range participants had higher baseline IgE [812 (IQR 632, 1747) IU/mL vs. 209 (IQR 134, 306) IU/mL] and received higher doses of omalizumab [750 (IQR 650, 750) mg] compared to within‐range participants [450 (IQR, 300, 600) mg]. At 6 months, improvements in Juniper 5‐item Asthma Control Questionnaire (ACQ‐5, 3.61 down to 2.01 for above‐range, 3.47 down to 1.93 for within‐range, P < 0.0001 for both) and Asthma Quality of Life Questionnaire (AQLQ mean score (3.22 up to 4.41 for above‐range, 3.71 up to 4.88 for within‐range, P < 0.0001) were observed in both groups. Forced expiratory volume in one second (FEV1 ) improved among above‐range participants. There was no difference in response between above‐range and within‐range participants. Above‐range participants due to either IgE alone or IgE and weight had similar improvements in ACQ‐5, AQLQ and FEV1 . Conclusions and Clinical Relevance: Patients with severe allergic asthma above recommended dosing criteria for omalizumab have significantly improved symptom control, quality of life and lung function to a similar degree to within‐range participants, achieved without dose escalation above 750 mg.